2020
DOI: 10.3390/diagnostics10090701
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis Diagnostics: Intensive Care Scoring Systems Superior to MicroRNA Biomarker Testing

Abstract: Sepsis represents a serious medical problem accounting for numerous deaths of critically ill patients in intensive care units (ICUs). An early, sensitive, and specific diagnosis is considered a key element for improving the outcome of sepsis patients. In addition to classical laboratory markers, ICU scoring systems and serum miRNAs are discussed as potential sepsis biomarkers. In the present prospective observational study, the suitability of miRNAs in sepsis diagnosis was tested based on proper validated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…showed the signi cant differences in the expression level of miR-193 in patients with sepsis in comparison with healthy controls [41]. The recent prospective observational study by the droplet digital PCR showed demonstrable signi cant differences in expression level of miR-193 between patients with septic intensive care, and non-septic intensive care [42]. MiR-193 play critical role in cell growth and in ammation, as well as survival by directly targeting the signal transducer and activator of transcription 3 (STAT3) [43,44].…”
Section: Discussionmentioning
confidence: 98%
“…showed the signi cant differences in the expression level of miR-193 in patients with sepsis in comparison with healthy controls [41]. The recent prospective observational study by the droplet digital PCR showed demonstrable signi cant differences in expression level of miR-193 between patients with septic intensive care, and non-septic intensive care [42]. MiR-193 play critical role in cell growth and in ammation, as well as survival by directly targeting the signal transducer and activator of transcription 3 (STAT3) [43,44].…”
Section: Discussionmentioning
confidence: 98%